Pengaruh Metode Pembelajaran Berbasis Game Edukatif terhadap Keaktifan Belajar Siswa SD Negeri 0101 Sibuhuan - Irma Sari Daulay; Puji Hertati Siregar; Salwa Hasibuan; Salsabila Siahaan; Sinniro Daulay; Yunita Sari Hasibuan (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Technological developments demand innovation in learning to suit the characteristics of Generation Z students, who tend to prefer visual, interactive, and technology-based learning. The low level of student learning activity at SD Negeri 0101 Sibuhuan in conventional learning encourages the need for more interesting media, one of which is through educational games. This study aims to determine the effect of using educational games on the learning activity of elementary school students. This study used a quantitative approach with a causal associative method. The sample was determined using probability sampling with simple random sampling. Data collection techniques included observation, questionnaires, and documentation, while data analysis used validity, reliability, normality, simple linear regression, and t-tests at a 5% significance level. The results showed that the average learning activity of students in classes that used educational games was 86, higher than that of conventional classes, which was 72. The regression equation Y = 35 + 0.6X with a coefficient of determination of 0.45 and a t-value of 4.12 > t-table 2.00 indicated a significant effect of the use of educational games on student learning activity. In conclusion, educational games have been proven to be effective in increasing student learning activity and can be used as an alternative innovative learning medium in elementary schools.